Historical Dictionary of Russian and Soviet Intelligence - Pringle, Robert W. (Historical dictionaries of intelligence and counterintelligence., 2015)
This second edition of Historical Dictionary of Russian and Soviet Intelligence is the only volume that lays out how Russian and Soviet intelligence works and how its operations have impacted Russian history. It covers Russian intelligence from the imperial period to the present focusing in greatest detail on Cold War espionage cases and the Putin-era intelligence community.